Relationship the Fuzzy P-Ideal with Some Fuzzy Subset of BH-Algebra - Abdulaali Neamah, Suad; ., . (International Journal of Engineering and Technology, 2018)
This  work  involved  some  studying ,we study and prove some theorems and a propositions which determine the relationships among the notion of  fuzzy p-ideal with the intersection, union, image of function, inverse function  and with some other fuzzy subsets of BH-algebra, also we gave some properties of this ideal of a BH-algebra.